محمد عبد الله عبد الكريم دراسة كفاءة مثبطات انزيم اليوريز في الترب المعاملة بمياه الصرف الصحي - عبداللهمحمد (University of Thi-Qar Journal of Science, 2019)
An incubation experiment was carried out to study the effect of municipal waste water on the efficiency of some urease inhibitors in soil. Waste water was collected from external basin of Hamdan industrial station, Basrah province and was passed through sand filter , then added to either loamy sand soil ( from AL-Zubair region) or silt loam soil ( from Qarma Ali region ) treated with urea at level of 200 mg N / Kg soil and with following urease inhibitor : phenylmercuric acetate ( PMA ), ammonium thiosulfate ( ATS ), or Tannic acid ( TA ). Urease inhibitors added to soil at concentration of 0 , 0.5 and 5.0 % w/w of urea. Shatt – AL-Arab water was used as control treatment of waste water. Treated soils incubated at 30 ± 2°C and urease activity was assayed after 5 and 25 days, then urease inhibition percentages were calculated. Results showed that efficiency of all urease inhibitors significantly increased in soil treated with waste water compared with those treated with Shatt – AL-Arab water. PMA caused highest urease inhibition compared with TA and ATS at all soils used. Data also revealed that highest urease inhibition was obtained in loamy sand soil compared with silt loam soil. Based on results obtained from incubation experiment, PMA at level of 5.0 % used in pot trial of tomato plant. Tomato seedlings transplanted in pots and irrigated with waste water or Shatt – AL-Arab water. Data of this experiment showed that dry matter and N – uptake of plant grown in soils receiving PMA were significantly higher than these growing in control ( untreated soils ), especially in silt loam soil. Plants treated with waste water show higher dry matter and N – uptake compared with plant treated with Shatt – AL-Arab water.